Resistance Training in Type II Diabetes Mellitus: Impact on Areas of Metabolic Dysfunction in Skeletal Muscle and Potential Impact on Bone - Richard J. Wood; Elizabeth C. O'Neill (Journal of Nutrition and Metabolism)
The prevalence of Type II Diabetes mellitus (T2DM) is increasing rapidly and will continue to be a major healthcare expenditure burden. As such, identification of effective lifestyle treatments is paramount. Skeletal muscle and bone display metabolic and functional disruption in T2DM. Skeletal muscle in T2DM is characterized by insulin resistance, impaired glycogen synthesis, impairments in mitochondria, and lipid accumulation. Bone quality in T2DM is decreased, potentially due to the effects of advanced glycation endproducts on collagen, impaired osteoblast activity, and lipid accumulation. Although exercise is widely recognized as an important component of treatment for T2DM, the focus has largely been on aerobic exercise. Emerging research suggests that resistance training (strength training) may impose potent and unique benefits in T2DM. The purpose of this review is to examine the role of resistance training in treating the dysfunction in skeletal muscle and the potential role for resistance training in treating the associated dysfunction in bone.